2021
DOI: 10.3390/magnetochemistry7100134
|View full text |Cite
|
Sign up to set email alerts
|

Pyridyl-Thioethers as Capping Ligands for the Design of Heteroleptic Fe(II) Complexes with Spin-Crossover Behavior

Abstract: Mononuclear heteroleptic complexes [Fe(tpma)(bimz)](ClO4)2 (1a), [Fe(tpma)(bimz)](BF4)2 (1b), [Fe(bpte)(bimz)](ClO4)2 (2a), and [Fe(bpte)(bimz)](BF4)2 (2b) (tpma = tris(2-pyridylmethyl)amine, bpte = S,S′-bis(2-pyridylmethyl)-1,2-thioethane, bimz = 2,2′-biimidazoline) were prepared by reacting the corresponding Fe(II) salts with stoichiometric amounts of the ligands. All complexes exhibit temperature-induced spin crossover (SCO), but the SCO temperature is substantially lower for complexes 1a and 1b as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has been shown that S-containing ligands can be utilised to obtain iron( ii ) spin crossover (SCO) complexes 1–13 in some of which the iron( ii ) centres have a {N 4 S 2 } coordination sphere. SCO materials can reversibly switch between the high spin (HS) and low spin (LS) states by and external stimulus, such as temperature, pressure, applied magnetic field, light irradiation, solvation, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that S-containing ligands can be utilised to obtain iron( ii ) spin crossover (SCO) complexes 1–13 in some of which the iron( ii ) centres have a {N 4 S 2 } coordination sphere. SCO materials can reversibly switch between the high spin (HS) and low spin (LS) states by and external stimulus, such as temperature, pressure, applied magnetic field, light irradiation, solvation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…1, and so far just a few examples of SCO-active octahedral iron( ii ) complexes comprising {N 4 S 2 } coordination spheres are known. 1–4,6–8,12,13 Moreover, the presence of S-donors in iron( ii ) metal complexes provides a double advantage to this type of systems. Firstly, a protection of the metallic centre avoiding its oxidation towards iron( iii ), which has already been observed in systems based on some redox-active sulphur ligands, 22 and secondly, maintaining the magnetic properties of these SCO-active systems.…”
Section: Introductionmentioning
confidence: 99%